Case Report: Preimplantation Genetic Testing for Meckel Syndrome Induced by Novel Compound Heterozygous Mutations of MKS1 - Lin, Tingting; Ma, Yongyi; Zhou, Danni; Sun, Liwei; Chen, Ke; Xiang, Yezhou; Tong, Keya; Jia, Chaoli; Jiang, Kean; Liu, Dongyun; Huang, Guoning (Frontiers in Genetics, 2022)
Meckel syndrome (MKS), also known as Meckel-Gruber syndrome, is a severe pleiotropic autosomal recessive developmental disorder caused by dysfunction of primary cilia during early embryogenesis. The diagnostic criteria are based on clinical variability and genetic heterogeneity. Mutations in the MKS1 gene constitute approximately 7% of all MKS cases. Herein, we present a non-consanguineous couple with three times of abnormal pregnancies as the fetuses showed MKS-related phenotypes of the central nervous system malformation and postaxial polydactyly. Whole-exome sequencing identified two novel heterozygous mutations of MKS1: c.350C>A and c.1408-14A>G. The nonsense mutation c.350C>A produced a premature stop codon and induced the truncation of MKS1 protein (p.S117*). Reverse transcription-polymerase chain reaction (RT-PCR) showed that c.1408-14A>G skipped exon 16 and encoded the mutant MKS1 p.E471Lfs*92. Functional studies showed that these two mutations disrupted the B9-C2 domain of the MKS1 protein and attenuated the interactions with B9D2, the essential component of the ciliary transition zone. The couple finally got a healthy baby through preimplantation genetic testing for monogenic disorder (PGT-M) with haplotype linkage analysis. Thus, this study expanded the mutation spectrum of MKS1 and elucidated the genetic heterogeneity of MKS1 in clinical cases.